Effect of self-confidence on high school student's social adjustment - Christanto, Flavianus A.; Susilo, Tritjahjo D.; Windrawanto, Yustinus (Universitas Pendidikan Ganesha, 2018)
The objective of this research was to evaluate whether self-confidence influenced students’ social adjustment significantly. One hundred and twenty students in Class X SMA Kristen 1 Salatiga was sampled and given questionnaires regarding self-confidence and social adjustment. The data was then analyzed quantitatively using simple linear regression. Results showed that there was a significant positive influence of self-confidence on social adjustment. Self-confidence explained 26.40% variation of social adjustment.